Role of GDNF, GFRα1 and GFAP in a Bifidobacterium-Intervention Induced Mouse Model of Intestinal Neuronal Dysplasia - Liu, Wei; Zhou, Tingting; Tian, Jinqiu; Yu, Xiaofang; Ren, Chuantao; Cao, Zengcai; Hou, Peimin; Zhang, Qiangye; Li, Aiwu (Frontiers in Pediatrics, 2022)
Objective: To investigate the effects of glial cell-derived neurotrophic factor (GDNF), GDNF family receptor alpha 1 (GFRα1), and glial fibrillary acidic protein (GFAP) on colonic motility in a mouse model of intestinal neuronal dysplasia by intervention with Bifidobacterium and to explore the influence of Bifidobacterium on enteric glial cells (EGCs). Methods: Western blotting and qRT-PCR were employed to detect the expression of GFRα1 and GFAP in colonic tissues of mice with or without Tlx2 mutations, and ELISA was used to detect the expression of GDNF in serum. IHC was used to detect the appearance of the ganglion cells. Subsequently, Tlx2 homozygous mutant (Tlx2-/-) mice were treated with Bifidobacterium. Colonic motility was measured before and after intervention by measuring the glass bead expelling time. The variations in abdominal circumference and GDNF, GFRα1, and GFAP expression were measured. In addition, 16SrRNA gene sequencing was performed to detect the abundance of the intestinal microbiota. Results: The mRNA and protein expression of GFRα1 and GFAP was decreased in the colonic tissues of Tlx2-/- mice and GDNF expression was decreased in serum compared with Tlx2+/- and WT mice. After confirming the colonization of Bifidobacterium by 16S rRNA gene sequencing, the expelling time and abdominal distension were ameliorated, and the expression of GFAP, GDNF, and GFRα1 was increased. Conclusions: The expression of GDNF, GFRα1, and GFAP is associated with colonic motility. The altered expression of EGC-related factors suggested that Bifidobacterium may be involved in the EGC activation process. The amelioration of IND symptoms after intervention with Bifidobacterium prompted the elicitation of adjuvant therapy.